Initial study on the combustion of palm wastes in a spouted bed - Taib, Mohamad Rozainee; Lim, S. Y.; Looi, S.; Ngo, S. P. (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Malaysia produces more than 35 million tones of palm wastes annually. These wastes, such as palm shells, palm fibers, and empty fruit brunches (EFB), which have high calorific values, could in turn be used for power and stream generation for plant usage. Palm wastes have a great potential as a renewable energy sources (Eighth Malaysia Plan, 2001-2005). Thus research was carried out to investigate the use of palm wastes as feed for combustion process in a spouted bed. Improper design and operating conditions of the combustor have detrimental effects on the boiler efficiency besides posing environmental problems. It was expected that spouted bed would demonstrate more efficient combustion of palm wastes. Investigations on the optimum combustion parameters in a SB included the determination of optimum bed height, amount of excess air ratio, and combustion temperatures. Results from this research showed that the secondary air was needed to improve the efficiency of the combustion process. Spouted bed demonstrated a very good mixing pattern of the sand and the palm wastes. At the bed height of 1.5 Dc and minimum spouting velocity of 2Ums, the optimum air factor for good combustion characteristics would be 1.6.